2003
DOI: 10.1111/j.1365-2265.2004.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of thyroid‐stimulating hormone (TSH) receptor antibody production following painless thyroiditis

Abstract: TBII elevation at the onset of PT in patients with a history of GD was detected by a sensitive hTBII assay. Destruction of the thyroid by PT may trigger GD recurrence in patients with a history of GD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…With regard to the destructive phase of the disease, evidence has accumulated in favor of an autoimmune process, as it was demonstrated that production of thyroid autoantibodies preceded thyroid dysfunction (14) and, indeed, this phase looks like postpartum thyroiditis (15) and silent thyroiditis. Moreover, Graves' disease occurring after biphasic thyroiditis does not seem to be specific to IFN-a, as several case reports have described it after subacute thyroiditis (16), postpartum thyroiditis (17,18) or spontaneous thyroiditis (16) or even after treatment of euthyroid goiter by 131 I (19). Progression towards Graves' disease is even more frequent for patients with a personal history of Graves' disease (16).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…With regard to the destructive phase of the disease, evidence has accumulated in favor of an autoimmune process, as it was demonstrated that production of thyroid autoantibodies preceded thyroid dysfunction (14) and, indeed, this phase looks like postpartum thyroiditis (15) and silent thyroiditis. Moreover, Graves' disease occurring after biphasic thyroiditis does not seem to be specific to IFN-a, as several case reports have described it after subacute thyroiditis (16), postpartum thyroiditis (17,18) or spontaneous thyroiditis (16) or even after treatment of euthyroid goiter by 131 I (19). Progression towards Graves' disease is even more frequent for patients with a personal history of Graves' disease (16).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, Graves' disease occurring after biphasic thyroiditis does not seem to be specific to IFN-a, as several case reports have described it after subacute thyroiditis (16), postpartum thyroiditis (17,18) or spontaneous thyroiditis (16) or even after treatment of euthyroid goiter by 131 I (19). Progression towards Graves' disease is even more frequent for patients with a personal history of Graves' disease (16). The TSHRAb production in susceptible individuals could thus be induced by the destruction of thyroid follicles that occurs during the course of thyroiditis, regardless of their cause.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a very weak positivity of TRAb2 before we started treatment. However, TRAb or TSAb have been reported to emerge in about 10% of patients with painless thyroiditis [8,9], therefore, we cannot make a definite differential diagnosis between GD and painless thyroiditis even if one of the thyroid autoantibodies is very weakly positive. The recommended cut-off value of TRAb2 used to be 2.0 IU/L and the sensitivity is 93.9% with 100% specificity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a rapid and fully automated electrochemiluminescence immunoassay for TRAb (Elecsys TRAb assay) was developed [10,11]. On the other hand, it has been reported that thyroid stimulating Ab (TSAb), which is measured using either TRAb or cAMP as the index, emerges in about 10% (or less) of PT cases [12,13,14,15], thus making the differential diagnosis between GD and PT difficult. Therefore, the gold standard for the differential diagnosis of these diseases includes thyroid uptake of Tc-99m or I-123.…”
mentioning
confidence: 99%